2007
DOI: 10.1007/s00249-007-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

A reduced amino acid alphabet for understanding and designing protein adaptation to mutation

Abstract: Protein sequence world is considerably larger than structure world. In consequence, numerous non-related sequences may adopt similar 3D folds and different kinds of amino acids may thus be found in similar 3D structures. By grouping together the 20 amino acids into a smaller number of representative residues with similar features, sequence world simplification may be achieved. This clustering hence defines a reduced amino acid alphabet (reduced AAA). Numerous works have shown that protein 3D structures are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 76 publications
1
52
0
Order By: Relevance
“…computed from distance between the amino acids using the Euclidean distance between the amino acid vectors. Similar approaches have been applied to Protein Blocks in a recent study [89]. We found that, with the increase of R values, amino acid composition of PUs deviated more and more from the average composition of proteins.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…computed from distance between the amino acids using the Euclidean distance between the amino acid vectors. Similar approaches have been applied to Protein Blocks in a recent study [89]. We found that, with the increase of R values, amino acid composition of PUs deviated more and more from the average composition of proteins.…”
Section: Resultssupporting
confidence: 63%
“…Protein Blocks (PBs) correspond to a set of 16 local prototypes [54,56,[85][86][87][88][89], labeled from a to p, of 5 residues length based on , dihedral angles description [90]. They were obtained by an unsupervised classifier similar to Kohonen Maps [91,92] and Hidden Markov Models [93].…”
Section: Protein Blocksmentioning
confidence: 99%
“…only 22% of the contacts of SC 4 are considered by C 8 . As we showed with reduced amino acid alphabets, the use of different definitions could lead to diverging results [123]. Distribution of the privileged interactions shows expected results, like the importance of Cysteine and of aromatic residues [105,106,[124][125][126][127][128][129][130].…”
Section: Discussionmentioning
confidence: 82%
“…They have been used both to describe the 3D protein backbones ( ) and to perform a local de Brevern et al, 2000de Brevern, 2005 structure prediction ( ; ; ; ; de Brevern et al, 2000de Brevern et al, 2004Dong et al, 2008Etchebest et al, 2005. PBs have proven their efficiency in the description and the prediction of long fragments ( ;Hansmann, 2008Benros et al, 2009;;;), to compare protein al., 2006de Brevern and Hazout, 2003de Brevern et al, 2002;), to build globular ( ) and transmembrane protein Tyagi et al, 2008Tyagi et al, 2006aTyagi et al, 2006bDong et al, 2007;), to define a reduced amino acid alphabet dedicated to de Brevern et al, 2005 mutation design ( ), to design peptides ( ), to define binding site signatures ( Etchebest et al, 2007Thomas et al, 2006Dudev and Lim, 2007 or to analyze protein contacts ( ). The features of this alphabet have been compared with those of 8 other structural Faure et al, 2009 alphabets showing clearly that our PB alphabet is highly informative, with the best predictive ability of those tested ( ).…”
Section: Introductionmentioning
confidence: 99%